2021
DOI: 10.1038/s41467-021-27475-2
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog-Interacting Protein is a multimodal antagonist of Hedgehog signalling

Abstract: Hedgehog (HH) morphogen signalling, crucial for cell growth and tissue patterning in animals, is initiated by the binding of dually lipidated HH ligands to cell surface receptors. Hedgehog-Interacting Protein (HHIP), the only reported secreted inhibitor of Sonic Hedgehog (SHH) signalling, binds directly to SHH with high nanomolar affinity, sequestering SHH. Here, we report the structure of the HHIP N-terminal domain (HHIP-N) in complex with a glycosaminoglycan (GAG). HHIP-N displays a unique bipartite fold wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…1e ), PTCH1 staining was generally enriched in cells between the GC basement membrane and the sTC layer. PTCH1 is both a receptor that activates Hh signaling, as well as a target of pathway activation 28 ; HHIP acts as a decoy receptor for Hh ligands, thereby having an inhibitory effect on activation 29 . Accordingly, PTCH1 and GLI1, both effectors of Hh signaling, were reduced in THBD + cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1e ), PTCH1 staining was generally enriched in cells between the GC basement membrane and the sTC layer. PTCH1 is both a receptor that activates Hh signaling, as well as a target of pathway activation 28 ; HHIP acts as a decoy receptor for Hh ligands, thereby having an inhibitory effect on activation 29 . Accordingly, PTCH1 and GLI1, both effectors of Hh signaling, were reduced in THBD + cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hedgehog interacting protein (HHIP) is a key regulator of fundamental processes in embryonic development and an endogenous antagonist of the Hedgehog signaling pathway 34,35 . Increasing studies evidenced that aberrant activation of the Hedgehog signaling pathway is one of the main causes of cancer progression, 36,37 especially serving as is a negative regulator of Hedgehog signaling pathway 35 .…”
Section: Discussionmentioning
confidence: 99%
“…When the HH signaling pathway is over-activated, the up-regulation of HHIP inhibits the activity of Hedgehog signaling pathway and results in a negative feedback regulation. HHIP binds with SHH in cell membrane and blocks the activation of the Hedgehog signaling pathway [ 37 ]. In the present study, we found that the downstream molecules of Hedgehog signaling pathway, Gli1 and Gli2, were down-regulated after the overexpression of lncRNA HHIP-AS1, which suppressed the osteogenic differentiation of BM-MSCs.…”
Section: Discussionmentioning
confidence: 99%